Konflik Batin dalam Struktur Kepribadian Tokoh Atsuko pada Novel Shojo Karya Minato Kanae: Tinjauan Psikologi Sastra - Reanitha, Reanitha; El Risman, Yunita; Nursidah, Nursidah (NAWA: Journal of Japanese Studies, 2025)
This study explores the internal conflicts within the personality structure of the Atsuko in Minato Kanae's novel Shojo through a literary psychological perspective. The research aims to examine how Atsuko’s psyche is shaped by her complex interactions with other characters and her environment. By utilizing Sigmund Freud’s psychoanalytic theory, particularly the concepts of the id, ego, and superego, this study analyzes how Atsuko’s internal conflicts stem from her reactions to external pressures and her personal desires. The study focuses on Atsuko’s struggles with her identity, her relationships with others, and her psychological responses to the events in the narrative. By applying psychological literary criticism, the research provides insights into how the character’s mental state is intricately portrayed, offering a deeper understanding of the human psyche and its representation in contemporary literature. Ultimately, this study highlights the intersection between psychology and literature, illustrating how fictional works can reflect real psychological experiences and conflicts.